Islam and Politics: Reflections on the Model of Government in the History of Classical Islamic Politics - Auliaurrahman; Usman, Zulkifli Abdurrahman (Scientific Journal for Nation Building, 2025)
This article shows that classical Islamic political history and governance reflect a dynamic model of Muslim government in accordance with the socio-political reality of each Muslim and in line with the changing times. This article is a literature study with data sources obtained from literature sources and online scientific journals. The analysis uses qualitative descriptive methods with approaches to Islamic history, Islamic political thought, historical sociology, and hermeneutics. The results of this article show that there are various governments in the history of Islamic politics. The pattern of the system of government also varies and changes along with changes in social and political dynamics in Islamic political history. On the basis of these findings, this article asserts that  any model of government system chosen by Muslims can be in line with Islam as long as it does not conflict with the basic principles, values, and norms of universal Islamic teachings.